Improvement of the conceptual principles of activity of the Ministry of Internal Affairs of Ukraine as a subject of the formation and development of the internal security environment of the state - K. L. Buhaichuk (Bulletin of Kharkiv National University of Internal Affairs)
The publication explores a new method of assessing the security environment based on indicators developed and approved by the Ministry of Internal Affairs of Ukraine. A SWOT analysis of the current state of the MIA system was conducted, on the basis of which its strengths and weaknesses have been identified, as well as possible external opportunities for development and the threats that accompany them.